Spatial Distribution of Low Birth Weight Infants (LBW) on Neonatal Mortality in East Java Province in 2020-2022 - Mawar Melindah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Infants have the highest risk of health problems during the neonatal period due to their vulnerable bodies. Infants with low birth weight (LBW) are one of the causes of neonatal mortality. The Infant Mortality Rate (IMR) in Indonesia is still high compared to other developing countries. Objective: The purpose of this study was to analyze the spatial distribution to determine the picture of LBW cases with neonatal deaths in East Java Province in 2020-2022. Method: This study uses a descriptive spatial analytic method using secondary data sourced from East Java Health Profile data in 2020, 2021, and 2022. The population and samples in this study were 38 districts/cities in East Java Province. Data processing uses bivariate maps through the QGIS 3.32.3 application. To support the hypothesis, statistical analysis was conducted using SPSS with Kolmogorov-Smirnov normality test and Pearson correlation test. Result: The results show that an increase in LBW will be followed by an increase in neonatal mortality cases. There is a significant relationship between neonatal mortality and LBW in East Java Province in 2020 (p value = 0.013 < 0.05); in 2021 (p value = 0.017 < 0.05), in 2022 (p value = 0.000 < 0.005). Conclusion: The conclusion of the study is Low Birth Weight Infants (LBW) with Neonatal Mortality Cases in East Java Province in 2020, 2021, to 2022 showed significant results so that, it can be interpreted that there is a strong enough relationship between variables. The relationship between variables produces a positive relationship, so it can be interpreted that an increase in LBW babies is followed by an increase in neonatal mortality cases.